2008
DOI: 10.1103/physrevlett.101.105001
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evidence of Undriven, Fast Reconnection in the Solar-Wind Interaction with Earth’s Magnetosphere: Formation of Electromagnetic Coherent Structures

Abstract: We give evidence for the first time of the onset of undriven fast, collisionless magnetic reconnection during the evolution of an initially homogeneous magnetic field advected in a sheared velocity field. We consider the interaction of the solar wind with the magnetospheric plasma at low latitude and show that reconnection takes place in the layer between adjacent vortices generated by the Kelvin-Helmholtz instability. This process generates coherent magnetic structures with a size comparable to the ion inerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…The development of vortex structures due to Kelvin-Helmholtz (K-H) instability in the shear flow of the magnetosheath/magnetopause has been studied by Matsumoto and Hoshino (2006) in the case of magnetic field perpendicular to the flow speed, and by Faganello et al (2008) in the case magnetic field oblique with respect to the flow speed (that is, a component of B parallel to the flow is present). It is found that a large scale vortex chain is formed first, and then small scale vortices due to secondary K-H instability and to Rayleigh-Taylor instability driven by the density gradient (Matsumoto and Hoshino 2006), or secondary reconnection due to the formation of magnetic inversion layers in between the large scale vortices (Faganello et al 2008). In the final stage, both simulations attain a multi-scale perturbed structure, which is very similar to the results of a turbulent cascade.…”
Section: Numerical Modeling Of Turbulence Effectsmentioning
confidence: 99%
“…The development of vortex structures due to Kelvin-Helmholtz (K-H) instability in the shear flow of the magnetosheath/magnetopause has been studied by Matsumoto and Hoshino (2006) in the case of magnetic field perpendicular to the flow speed, and by Faganello et al (2008) in the case magnetic field oblique with respect to the flow speed (that is, a component of B parallel to the flow is present). It is found that a large scale vortex chain is formed first, and then small scale vortices due to secondary K-H instability and to Rayleigh-Taylor instability driven by the density gradient (Matsumoto and Hoshino 2006), or secondary reconnection due to the formation of magnetic inversion layers in between the large scale vortices (Faganello et al 2008). In the final stage, both simulations attain a multi-scale perturbed structure, which is very similar to the results of a turbulent cascade.…”
Section: Numerical Modeling Of Turbulence Effectsmentioning
confidence: 99%
“…[] have summarized two types of this so‐called vortex‐induced reconnection (VIR). Type‐I VIR occurs when the in‐plane field is initially antiparallel across the velocity shear layer [e.g., Pu et al ., ; Knoll and Chacón , ; Nakamura et al ., , ], while type‐II VIR is driven within the highly rolled‐up vortex where the wrapped field lines produce thin current layers [e.g., Nykyri and Otto , ; Nakamura and Fujimoto , ; Faganello et al ., ]. Since type‐I VIR is the main focus of this study, for the rest of this paper, we simply refer to this as VIR.…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions are drawn for the diffusion process, and does not rule out the possible role of KH instability to trigger magnetic reconnection and associated mass transfer. 35,36 The next step in this study is to identify the respective role of electric and magnetic fluctuation, as well as their coupling. A robust methodology to identify and subtract the mean fluid velocity would also allow to investigate the j ?…”
Section: Discussionmentioning
confidence: 99%